Kajian Interaksi Antar Obat Terhadap Profil Glikemik Pada Pasien Diabetes Rawat Inap Rumah Sakit Islam Sultan Agung Semarang - Willi Wahyu Timur; Rikma Eliya Ussa; Naniek Widyaningrum (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Drug interactions are conditions when the use of drugs can affect the effects of other drugs pharmacokinetic or pharmacodynamically. Effects caused by interactions between drugs in the form of expected effects or adverse effects for patients. In general, drug interactions occur in patients with diabetes mellitus because they receive treatment therapy for more than one kind of drug, so there is a chance for interactions that will interfere with controlling sugar levels. This study aims to see the relationship between drug interactions with blood sugar levels. This type of research is observational with a descriptive analytic design using retrospective data collection. The population in this study were all inpatients with diabetes mellitus without or with comorbidities of Hypertension, Dyslipidemia, Dyspepsia, Congestive Heart Failure, and Coronary Artery Disease at Sultan Agung Islamic Hospital, Semarang. Samples were taken from as many as 51 patients with the purposive sampling technique. Data was collected by collecting inpatient medical records. Statistical analysis using the Chi-Square test. Based on statistical analysis, it was found that the p-value of 0.001 can be concluded that there is an interactive relationship between drugs and blood sugar levels in inpatients with diabetes at Sultan Agung Islamic Hospital, Semarang.